Awareness of Students on the Usefulness of ICT Tools in Education: The Case of EMU IT Students - Tochukwu, Ilodigwe Udoka (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Educational technology importance and its use is widely becoming a norm in the traditional classroom, by both learners and teachers respectively. The significance of this dissertation focused on investigating EMU IT students‘ awareness on the usefulness and use of ICT tools. This dissertation also studied various students‘ awareness and other factors like skills in usage of ICT tools, purpose of usage etc., based on age, gender and class levels of the participants. The study also elaborates the basic trends of ICT, and the sync between ICT and education for pedagogical development. Data were elicited from participants through the use of questionnaires and interview questions. 120 Participants were all analyzed based on gender, age and class level on the awareness of ICT. Analyses were carried out on the gathered data using t-test, ANOVA, standard deviations and percentages. Also significant differences were conducted on variable factors based on participant‘s demographic characteristics. The findings of this dissertation proved the awareness of EMU IT students on the usefulness of ICT tools are on a high scale and there were no significant differences on their awareness of ICT use and e-learning based on age, gender and class level. In a slim case, some data proved the existence of a significant difference on the awareness of student on usefulness of ICT and its use based on class levels. Keywords Instructional Technology, Distance Education, E-learning, Information Communication Technology, Perception.

ÖZ: Eğitim teknolojisi önemi ve kullanımı yaygın sırasıyla hem öğrenciler ve öğretmenler tarafından, geleneksel sınıfta bir norm haline gelmektedir. Bu tez önemi yararlılığı ve BİT araçlarının kullanımına ilişkin DAÜ Bilişim öğrencilerin farkındalığını soruşturma üzerinde duruldu. Bu tez aynı zamanda çeşitli öğrencilerin farkındalık ve katılımcıların yaş, cinsiyet ve sınıf düzeylerine göre BİT araçları, vb kullanım amacına, kullanımı becerileri gibi diğer faktörler incelendi. Çalışmada ayrıca BİT temel eğilimleri ve pedagojik gelişimi için BİT ve eğitim arasındaki senkronizasyon ayrıntılı. Veriler anket ve mülakat soruları kullanımı yoluyla katılımcıların ortaya çıkarıldı. Yüz yirmi Katılımcılar tüm bilgi iletişim teknolojisi araçlarının bilinci cinsiyet, yaş ve sınıf seviyesine göre analiz edilmiştir. Analiz t-testi, ANOVA, standart sapmalar ve yüzdeleri kullanılarak toplanan veriler üzerinde yürütülmüştür. Ayrıca önemli farklılıklar katılımcının demografik özelliklerine göre değişken faktörlere üzerinde yürütülmüştür. Bu tez bulguları, yüksek ölçekte olan BİT araçlarının kullanışlılığı DAÜ BT öğrencilerinin farkındalık kanıtladı ve yaş, cinsiyet ve sınıf seviyesine göre BİT kullanımı ve e-öğrenme kendi bilinci üzerinde önemli farklılıklar vardı. Ince bir durumda, bazı veriler sınıf düzeylerine göre BİT yararlılığı ve kullanımına ilişkin öğrenci bilinci üzerinde önemli bir farklılığın varlığını kanıtladı. Anahtar Kelimeler Öğretim Teknolojileri, Uzaktan Eğitim, E-öğrenme, Bilgi İletişim Teknolojileri, Algı.
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Information and Communication Technology in Education, 2015. Supervisor: Dr. Fatma Tansu Hocanın.
Keywords: Information and Communication Technology in Education; Computer-assisted instruction - Computer programs; Education - Computer network resources; Teaching - Computer network resources; Instructional Technology; Distance Education; E-learning; Information Communication Technology; Perception